Non destructive evaluation of new concrete construction - Gupta, A. K. (Journal of Structural Engineering, 2025)
Non Destructive Testing (NDT) plays an important role in quality auditing of new and structural assessment of old concrete structures. NDT being indirect techniques require correlation of the property observed and the desired property of the concrete. A good number of factors can alter this correlation, therefore it is common to use NDT qualitatively for assessment of old structures. In case of new concrete construction environmental factors remain insignificant to alter the correlation. Results of Non Destructive Testing of some new concrete construction with the age between 4 days to 1 year using common techniques i.e., Schmidt Rebound Hammer, Ultrasonic Pulse Velocity and Core testing and available lab testing records are presented. In certain cases it is observed that strength of new concrete construction observed by NDT is close to destructive tests conducted in the lab.